(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2012)
Lawsuits are proliferating in the Federal Court arguing over the legitimacy of levying employer’s contributions on certain sums paid by companies which, in principle, do not correspond to consideration for actual work performed. Based on this premise - that the payment does not correspond to actual work done by the employee - the conclusion is that these are indemnity payments, which could not be included in the economic basis for levying the social contribution owed by companies on the salary paid to their employees. The amounts in question include unpaid notice, vacations and an additional one-third, the first fifteen days of the employee’s leave in the event of sickness benefit or accident benefit, maternity pay, among others. This claim has been relatively successful in the courts. With all due respect, the mistake in this reasoning lies in the premise: remuneration does not depend on the employee actually working in order to be characterized as such.